O acesso à cidade: questões sócio-econômicas da cidade de Cáceres com enfoque na Praça da Feira - Dan, Vivian Lara Cáceres (2010)
This dissertation examines the enormous contradictions of capitalism manifested in the city of Cáceres and increasing social inequality in this place. The text relates the economy, spatial organization, social issues and how the bourgeois class acts in local politics. So we can show that inequality, those who are producing and who it affects and interests. To understand what happens in this Praça da Feira, a poverty place, neglect, the affront of people, and still approach the performance of the social sind , religious the when police becomes and example of how this espace outward social inequalities lived in this society and how the local elite promotes strategies of suffocation in ths place. Discussing how the state and organized society act to stifle a place that disturb , or to highlight the social policies that attempt to soften the social problems, or even approaching the ordering strategis of urban spaces that town. These agreed can be faced as a factor of segregates politics and inequality experienced by society as well as understande how these practices are directed to serve to the interests of the local elite. The relation of the theoretical and methodological reflections is anchored by Carlos Nelson Coutinho, Ronaldo Coutinho, Sonia Mendonça, Cecília Coimbra, Roberto Lobato Correa, Virgínia Fontes, Jose de Souza Martins, Karel Kosik, Milton Santos, among other that inspire the agreement of this reality. This way join theoretical assumptions to the qualitative research based on a surved of bibliographies on the subject, collecting data from nespapers, magazines, proceedings and requirements of the city council, laws, projects, interviews, police reports, maps, data in official sites as INCRA, IBAMA, IBGE and interviews among others